Evaluasi Program Gerdu Kempling Sebagai Upaya Penanggulangan Kemiskinan di Kota Semarang (Studi Kasus: Kelurahan Palebon, Kecamatan Pedurungan) - Rahmawati, Agustina (Sawala : Jurnal Administrasi Negara, 2018)
Integrated Movement Program in the Field of Health, Economy, Education, Infrastructure, and Environment or abbreviated Gerdu Kempling Semarang City Government was launched based on Local Regulation No. 4 of 2008 on Poverty Alleviation and Instruction of Mayor of Semarang number 054/2/2011 on Acceleration of Poverty Reduction Semarang City. This program targets poverty to fall by 2% every year. To achieve these objectives, Semarang City government cooperates with private parties, state-owned enterprises, universities and NGOs. One of the kelurahans who have implemented Gerdu Kempling program is the Palebon village. The Village get CSR from PDAM Tirta Moedal, PT Telkom and Rotary Club for Rp 200 million which is used to carry out empowerment activities. However, there are some problems that affect the outcome of the Gerdu Kempling program in the Palebon subdistrict. Based on this study, this study evaluates the performance of Gerdu Kempling program in Palebon sub-district by observing the phenomenon of input, process, output, and outcome. The approach used is descriptive qualitative with interview data collection method, questionnaire, and documentation study. The data already collected will be presented and reduced then drawn conclusions. The results of this research are that the program input is correct, but the main problem is in the process of improper policy transformation which involves short time of empowerment that is only 1 year, the types of activities that are not in accordance with the needs of the community and not sustainable, and monitoring evaluation only administrative and no measure of success in the program. These problems affect the results of community appraisal of outputs and outcomes where most people state that they are not yet self-sufficient through the Gerdu Kempling program. However, the community also assessed the greatest impact felt is the field of environment and infrastructure.Keywords: Poverty, Gerdu Kempling, Village